Identification of Adipogenesis Subgroups and Immune Infiltration Characteristics in Diabetic Peripheral Neuropathy - Yumin Lin; Liyuan Qu; Jintao Wu; Meicen Pu; Yijuan Huang; Ying Cao (Journal of Immunology Research)
Dysregulation of adipogenesis is related to diabetic peripheral neuropathy (DPN) pathogenesis, which may be mediated by immune infiltration. Nevertheless, the expression patterns of multiple adipogenesis-related genes and the differences of immune infiltration in different lipid metabolism levels remain unknown. GSE95849, a gene expression matrix containing DPN patients and healthy participants, was downloaded from Gene Expression Omnibus (GEO) database. Differentially expressed adipogenesis-related genes (DEARGs) were screened by overlapping the adipogenesis-related genes with differentially expressed genes (DEGs). DPN patients from GSE24290 and GSE148059 were divided into two adipogenesis subgroups according to the expression of DEARGs. The single-sample gene set enrichment analysis (ssGSEA) was used to estimate the abundance of the immune cells between two subgroups. The analysis of immune infiltration suggested that a variety of immune cells and immune processes were elevated in the high expression group of DEARGs. The differentially expressed genes of the two subgroups were mainly enriched in biological processes and signaling pathways related to lipid metabolism. PPARG, FABP4, LIPE, FASN, SCD, DGAT2, PNPLA2, ADIPOQ, LEP, and CEBPA were identified as the hub genes of the two subgroups, whose related transcription factors (TFs) and miRNAs were predicted. An immunohistochemical assay was used to verify the expression of hub genes in DPN nerve tissues. Our comprehensive analysis of adipogenesis subgroups in DPN illustrated that different expression patterns of DEARGs may lead to different immune and inflammatory states. The identification of DEARGs may help to further distinguish the different characteristics of DPN patients and lay the foundation for targeted treatment. Our findings may bring a novel perspective to the diagnosis and treatment of DPN patients.